The Northwest Passage in Transit - Griffiths, Franklyn (International journal (Toronto), 1999)
A CONSTRUCTION OF SOUTHERN MINDS, the Northwest Passage has long been the site of exploration in reality and in imagination. This article is an exercise in the imagination. For gritty detail on navigation in polar waters you will have to look elsewhere. What I am about to consider is not the Northwest Passage and what is being done there, but rather its changing context and the elements of an alternative construction that might now be put on it. For some decades the waters of the Canadian Arctic archipelago have been construed largely in terms of conflict between a coastal state, Canada, which would like to exercise exclusive jurisdiction, and major maritime powers, principally the United States, whose chief aim is to maintain freedom of navigation. This frame of reference is proving to be not that well suited to the requirements of emergent collective action in the circumpolar north. The received thinking is also being overtaken by far broader developments, the combined effect of which is very difficult to discern. In an era of global change the Northwest Passage is not exempt: it and most everything connected with it is in transit from a familiar past to an indeterminate future. In hopes of contributing to the search for better ways of doing things together in the Arctic, I will briefly explore the Northwest Passage for an alternative construction more in keeping with the times. But first, the received thinking. Whether the contemporary law of the sea is seen as an instrument to manage the world's oceans or merely as a set of prescriptions and prescriptions for state action, freedom of navigation in Arctic waters is taking its own course and is not what it used to be. Where the Northwest Passage in particular is concerned, with active United States participation a regional practice is developing which challenges the view that Arctic issues are properly resolved on the basis of extraregional requirements. Nor, given the continued growth of multilateral Arctic co-operation in which all have a stake, can the United States expect to contest the Canadian sovereignty claim as readily as once it might have. Residual Canadian-United States differences over the Passage are being embedded in a circumpolar context which crimps the affirmation and exercise of rights to freedom of navigation. Meanwhile, to the degree that northerners continue to be empowered, commercial navigation in Arctic waters will have to conform to new and more telling regional and local requirements - for instance in marine transportation ventures in waters bordered by Greenland and a Nunavut to which the Canadian government will have to pay heed. In sum, the inclination of the United States and other Arctic governments to protect the freedom of the seas by decoupling legal and military affairs from civil co-operation in the region eases the way to a collaboration which can only constrict the freedom of action of states and hence freedom of navigation in this part of the world. (f.9) In 1995, the United States navy dedicated a Sturgeon-class SSN, before decommissioning, for Arctic research under the SCICEX programme, which is to terminate in 1999. SSNs enter and exit the Arctic Ocean only via Fram Strait and Bering Strait. Unless otherwise invited, they operate only in waters beyond the 200-mile exclusive economic zone (EEZ) of the Arctic states, as is required by the law of the sea. Although only United States nationals are on board, these SSNs have conducted research or performed experiments for scientists in foreign countries. In 1998, the Bedford Institute of Oceanography in Halifax proposed that a SCICEX submarine come into the Canadian Arctic EEZ to within perhaps 30 miles of the archipelago, to conduct studies of the Canadian Basin and continental slope there. Personal communications with Gary Brass, Arctic Research Commission, Washington, DC, 18 May 1998, and John N. Smith, Bedford Institute, 24 June 1998. The proposal was to come from the Canadian government and was the subject of interdepartmental discussion in Ottawa. It had not been acted upon as of January 1999. Personal communications with John N. Smith, 12 January 1999, and [Howard Strauss], 13 January 1999. The Canadian Coast Guard, for its part, has been planning a joint research project in which the newest United States Arctic research platform, the Coast Guard icebreaker Healy, would come into the archipelago to assist in establishing its capabilities and in conducting hull studies, when sea trials begin in 1999. Personal communication with [Peter Timonin], 11 January 1999.